(3JPcQg Chdi GdCdHGH aj GSJjaGA GdYed HGdGSWQdGHs - (3CHh GdbGSe GdRHjQ Hf CMeO Hf EHQGgje Hf GdRHjQ, GdKbaj GdbGVjs
(3ChdgG (B:s
(3HYO GdOjHGLI aEfi deG QCjJ GdfGS deG JcdehG ai GdbOje hGdMOjK YdiGdBdg GdfLhejI GdeYQhag HGdGSWQdGH hVYhG YdjgG QSGFd s
(3BNQgG (B:s
(3ddGSJZfGA Yf Pdc HGdUajMI GdLGeYI GdehVhYI ai ReGffG hGdehLhOI HHdGOfG hgj GdYQhV GdJi ef EfTGA TjNfG CHj Ydi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B1025 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B19 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjg (B((3ejbGJ (B173(2)) s
Keywords: (3Gdadcs